2019
DOI: 10.1016/j.molcel.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Global Positioning System: Understanding Long Noncoding RNAs through Subcellular Localization

Abstract: The localization of long noncoding RNAs (lncRNAs) within the cell is the primary determinant of their molecular functions. LncRNAs are often thought of as chromatin-restricted regulators of gene transcription and chromatin structure. However, a rich population of cytoplasmic lncRNAs has come to light, with diverse roles including translational regulation, signaling, and respiration. RNA maps of increasing resolution and scope are revealing a subcellular world of highly specific localization patterns and hint a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
152
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(168 citation statements)
references
References 178 publications
5
152
0
2
Order By: Relevance
“…The function of lncRNA depends mainly on its subcellular localization. 21 Here, by performing nuclear-cytoplasmic fractionation and FISH assays, we found that ARAP1-AS1 was predominately located in the nucleus in CC cells. Given that nuclear lncRNA regulated gene expression mainly via formation of functional lncRNA-protein complexes, 12 we then used in silico prediction combined with pull-down assay to identify ARAP1-AS1-binding proteins, and found that ARAP1-AS1 was able to directly bind to PSF.…”
Section: Discussionmentioning
confidence: 74%
“…The function of lncRNA depends mainly on its subcellular localization. 21 Here, by performing nuclear-cytoplasmic fractionation and FISH assays, we found that ARAP1-AS1 was predominately located in the nucleus in CC cells. Given that nuclear lncRNA regulated gene expression mainly via formation of functional lncRNA-protein complexes, 12 we then used in silico prediction combined with pull-down assay to identify ARAP1-AS1-binding proteins, and found that ARAP1-AS1 was able to directly bind to PSF.…”
Section: Discussionmentioning
confidence: 74%
“…The molecular functions of lncRNAs are primarily determined by their subcellular localization [41]. Thus, to further unravel the downstream effects of SNHG12, we analyzed the localization of SNHG12 in TMZ-resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Functions of lncRNAs are associated with their subcellular fates. Web servers can assist in quickly assessing experimentally determined or predictive RNA-RNA interactions [204] or even RNA-protein interactions [205,206]. Depending on the subcellular or extracellular compartmental localization of a lncRNA, this patterning will elude to the regulatory role of the gene, as well as how a lncRNA might execute its function [207][208][209].…”
Section: Subcellular Localization and Binding Partnersmentioning
confidence: 99%